ANALISIS PERMINTAAN AYAM POTONG (BROILER) OLEH PEOAGANG PENGECER DAN TINGKAT KONSUMSI RUMAH TANGGA TERHADAP DAGING AYAM POTONG 01 KOTA BENGKULU - Purwoko, Agus; Romdon, M Mustopa; Subagio, . (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2004)
The objectives of this research were to analyze factors influencing broiler meat demanded by retailers and households. The research was conducted at Pasar Minggu, Bengkulu city. Two sampling methods were used,i.e, Simple Random Sampling for selecting 29 retailers and Accidental Sampling for selecting 58 households (two households for each retailer). Multiple regression model which then estimated with OLS was applied in estimating the objectives. Results showed that factors partially influencing retailer' demand for broiler meat were broiler price at producers/distributors (X3) and capital (X6), while broiler meat price at consumers (X4) and plastic bag price (X5) were not significant factors. At household level, family members (X2), total familiy income (X3) and broiler meat price (X4) were significantly influencing households to consume broiler meat, while household education ataianment (X1), domestic chicken (buras) meat price (X5), tempe price (X6) and gold fish price (X7) were not.